PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA PERUSAHAAN (Studi Kasus Pada Perusahaan yang Terdaftar dalam Peserta Corporate Governance Perception Index (CGPI) Tahun 2010-2012) - Nuryasti, Hanik; Achmad, Komarudin (Jurnal Ilmiah Mahasiswa FEB, 2016)
The research aims to understand the influence of good corporate governance and leverage on the performance of the company. The company’s performance was measured based on return on equity ( ROE ). The good corporate governance measured based on Corporate Governance Perception Index (CGPI) from 2010 to 2012 which is published by the Indonesian Institute for Corporate Governance (IICG). Th leverage was measured based on Debt to Assets Ratio (DAR). The data was gathered using purposive sampling method sample with 57 samples in total. The result of this research proved that the increasing of good corporate governance affect the improving of company’s performance. Meanwhile, the increase in the leverage affect the declining of company’s performance.   The   keywords:   good   corporate   governance,  leverage,   performance   of  the company.